(untitled) (Journal of Science and Technology, 2016)
Acute intestinal obstruction is a very rare condition in pregnancy. It poses a diagnostic problem because it may mimic pregnancy – related symptoms. The following paper describes a case of acute intestinal obstruction in late pregnancy which resulted in irreversible shock and death soon after delivery. Lessons from the mode of presentation of this condition are discussed to highlight this rare complication of pregnancy.